2019
DOI: 10.1097/rct.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Time-of-Flight–Magnetic Resonance Angiography From Silent Scan Magnetic Resonance Angiography in Depiction of Arteriovenous Malformation of the Brain

Abstract: Objective Silent magnetic resonance angiography (MRA) was compared with time-of-flight (TOF)–MRA in imaging of arteriovenous malformations (AVMs) of the brain. Methods Thirty-five consecutive patients with AVMs of the brain were included. Quantitative analyses were performed by measuring both signal-to-noise ratio and contrast-to-noise ratio of the nidus. Qualitative analysis (scores 1–4) was performed by evaluating depictions of feeding arteries and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Seventy-three out of all 81 draining veins (90.1%) were detected on silent MRA in our study. Comparably, previous studies have also found that a small portion of draining veins of BAVM could not be visualized on silent MRA [11][12][13][14], yet few tried to explain this phenomenon. In the current study, the non-visualized draining veins were all observed more than 4 frames after nidal visualization on DSA, suggesting that those missing draining veins in silent MRA may be a consequence of slow blood flow.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Seventy-three out of all 81 draining veins (90.1%) were detected on silent MRA in our study. Comparably, previous studies have also found that a small portion of draining veins of BAVM could not be visualized on silent MRA [11][12][13][14], yet few tried to explain this phenomenon. In the current study, the non-visualized draining veins were all observed more than 4 frames after nidal visualization on DSA, suggesting that those missing draining veins in silent MRA may be a consequence of slow blood flow.…”
Section: Discussionmentioning
confidence: 87%
“…Silent MR angiography is a new imaging approach based on arterial spin labeling (ASL) and zero time echo (ZTE) techniques and does not require a contrast agent [11]. Several studies have reported that silent MRA achieved better performance in depicting the nidus and draining veins of BAVM compared to time-of-flight MR angiography (TOF MRA) [12][13][14]. In these studies, a portion of the draining veins of BAVM still could not be observed on silent MRA.…”
Section: Introductionmentioning
confidence: 99%
“…However, this invasive technique carries a risk of neurological complications and adverse reactions associated with the contrast agent as well as the exposure to ionizing radiation during the procedure. Various non-or less-invasive imaging techniques have thus been applied to the evaluation of AVS [12][13][14][15][16][17][18][19][20][21][22]. Time-of-flight (TOF)-MRA has been the most widely used of these in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] MRA with ultrashort echo time (UTE-MRA) reduces metal artifact,[ 3 , 7 - 9 ] and its usefulness is reported for the assessment of the internal flow in the intracranial stent,[ 4 , 10 ] moyamoya disease,[ 12 ] and arteriovenous malformation. [ 13 ] Besides, 1.5T UTE-MRA revealed the artery in the vicinity of a clip,[ 5 ] but the obtained image is too rough to evaluate the aneurysm remnant, and its description range is too narrow to assess the cerebral vasospasm especially of the peripheral portion. Therefore, 1.5T UTE-MRA does not yet have the clinically required quality as a usual follow-up after clipping.…”
Section: Image Reportmentioning
confidence: 99%